What's a SNP between friends: The lineage of Clostridioides difficile R20291 can effect research outcomes. (October 2021) - Monteford, Jorge; Bilverstone, Terry W.; Ingle, Patrick; Philip, Sheryl; Kuehne, Sarah A.; Minton, Nigel P.
Abstract: Clostridioides difficile R20291 is the most studied PCR-Ribotype 027 isolate. The two predominant lineages of this hypervirulent strain, however, exhibit substantive phenotypic differences and possess genomes that differ by a small number of nucleotide changes. It is important that the source of R20291 is taken into account in research outcomes. Highlights: Two phenotypically distinct lineages of C. difficile R20291 are in circulation. Affected are gene transfer, motility, sporulation, biofilm and toxin production. The differences are due to a small number of single nucleotide genomic changes. These findings underline the importance of appropriately maintaining stock cultures. The source of R20291 should be stated in any investigation.